Tourism as a Catalyst for Socio-Economic Transformation: Insights from Sharangkot, Kaski - Sharma, Laxmi Kanta (Journal of Development and Administrative Studies, 2020)
This research examines tourism’s impact on Sharangkot’s socio-economic landscape, a key destination in Nepal’s thriving tourism sector. Focusing on communities transitioning from agriculture to tourism, the study used a quantitative method, surveying 100 local households. It analyzed the correlation between tourism and socio-economic variables, considering both benefits (like job creation and infrastructural growth) and challenges (such as inflation and environmental issues. Results show tourism significantly improves Sharangkot’s living standards, bringing economic advantages and infrastructural enhancements, but also raising costs and environmental concerns. The study underscores the need for sustainable tourism strategies that harmonize economic and environmental interests. It also suggests further research to delve deeper into the complex interplay between tourism and socio-economic factors in Sharangkot.